Requirements engineering practices model for software development outsourcing issues / Javed Iqbal - Javed , Iqbal (2016)
Software Development Outsourcing (SDO) has become a common practice due to its reported benefits like cost reduction, process improvement, and dealing with a lack of required skills. The trend for outsourcing the software development projects is growing day by day. However, a considerable proportion of such outsourcing projects fails to materialize the anticipated benefits. The reasons for the failure are often traced back to the Requirements Engineering (RE) process. This establishes the importance of the RE for SDO. The geographical dispersion of the stakeholders is the basic source of issues during the RE process for SDO. The delayed responses, unawareness from the effects of new system implementation, poorly defined requirements, and incomplete requirements are some of such important issues. The primary focus of this research work is to develop and evaluate the sets of the best RE practices to address the frequently or commonly occurring issues of the SDO RE process. Therefore, issues of the RE process for SDO and relevant RE practices to address those issues have been identified from the literature. To incorporate the industrial perspective, SDO practitioners have been solicited for reporting the additional issues and relevant RE practices to address the issues. Then, frequently occurring issues have been extracted, ranked, the root causes for those issues have been identified, sets of the best RE practices have been recommended to address the corresponding issues and have been evaluated. The sets of the best RE practices are referred to as Requirements Engineering Practices (REP) Model. To accomplish the research objectives, an extensive Systematic Literature Review has been performed and questionnaire-based surveys have been conducted with the SDO practitioners. The Delphi method has been employed to develop a consensus among the practitioners. By applying the Delphi method and the Cut-off value method, frequently occurring issues have been filtered out and ranked. The Root Cause Analysis has been performed to discover the root causes for frequently occurring issues and for recommending the relevant RE practices to address those issues. The REP Model is evaluated from: i) The academic point of view through the expert panel of 3 researchers and academicians, ii) The industrial perspective through 11 experienced SDO practitioners. Three criteria for evaluation from the academic point of view are: i) Completeness, ii) Practicality, and iii) Usefulness. The criterion for the industrial evaluation is ‘usefulness of the recommended RE practice(s) to address the corresponding issue of the RE process for SDO in the case of the respective root cause’. The REP Model presents frequently occurring issues of the SDO RE process, provides the Category-wise and the Overall ranking of those issues, ranks the categories of the issues, specifies the root causes for those issues and hence maps the issues to the root causes and the relevant best RE practices to address the respective issues. Thus, the REP Model supports the RE process for SDO, and helps to avoid the adoption of random and ad-hoc RE practices for dealing with the common issues of this process.